A Quick Overview on Initial Enlargement of Filtrations - Peralta Hernández, Liliana (Pädi Boletín Científico de Ciencias Básicas e Ingenierías del ICBI, 2018)
We describe, thought of a particular example, the meaning of initial enlargement of filtration, this means, when we expand a filtration with a sigma algebra.